Factors influencing the uptake of a mass media intervention to improve child feeding in Bangladesh - Kim, Sunny S.; Roopnaraine, Terry; Nguyen, Phuong Hong; Saha, Kuntal K.; Bhuiyan, Mahbubul I.; Menon, Purnima (John Wiley & Sons, 2018)
Mass media are increasingly used to deliver health messages to promote social and behaviour change, but there has been little evidence of mass media use for improving a set of child feeding practices, other than campaigns to promote breastfeeding. This study aimed to examine the factors influencing the uptake of infant and young child feeding messages promoted in TV spots that were launched and aired nationwide in Bangladesh.